Neuropathic pain questionnaire and neuropathic pain questionnaire-short form: Translation, reliability, and validation study of the Turkish version - Yurdakul, Ozan Volkan; Rezvani, Aylin; Küçükakkaş, Okan; Tolu, Sena; Kılıçoğlu, Mehmet Serkan; Aydın, Teoman (Turkish Neurosurgical Society, 2019)
AIM: To perform reliability and validity studies of the Neuropathic Pain Questionnaire (NPQ) and NPQ-Short Form (SF) in the Turkish language. MATERIAL and METHODS: The Turkish translation and cross-cultural validation were performed. Then, 101 patients (36 males, 65 females; mean age: 50.4 ± 14.49; range: 20-87) with chronic pain were asked to fill out a pack of questionnaires, including the NPQ, NPQ-SF, Douleur Neuropathique 4 (DN4), Leeds Assessment of Neuropathic Symptoms (LANSS), and Numeric Rating Scale (NRS). A subgroup of 41 patients (11 males, 30 females) completed the NPQ and NPQ-SF for the second time after 3 days by telephone. Internal consistency was tested by Cronbach's-? and test-retest reliability was assessed by calculating the intraclass correlation coefficients (ICC). Construct validity was assessed by comparing NPQ, NPQ-SF, and NRS. Concurrent validity was tested by comparing NPQ, NPQ-SF, DN4, and LANSS. RESULTS: Internal consistency by Cronbach's-? was 0.84 and 0.67 for the NPQ and NPQ-SF, respectively, indicating adequate and low internal consistency, respectively. ICC was 0.96 (p < 0.001; 95% confidence interval [CI], 0.95-0.97) for NPQ and 0.97 (p < 0.001; 95% CI, 0.95-0.97) for NPQ-SF, indicating a high test-retest reliability for both questionnaires. CONCLUSION: The Turkish versions of NPQ and NPQ-SF were reliable and valid for patients with chronic pain. To our knowledge, this is the first Turkish adaptation and test of the reliability and validity of the NPQ and NPQ-SF (short-form). These questionnaires could potentially help clinicians who seek to assess neuropathic pain for clinical and investigational purposes.
Keywords: Neuropathic Pain Questionnaire; Cross-Cultural Adaptation; NPQ; Reliability; Validity